The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep44761
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to selenomethionine causes selenocysteine misincorporation and protein aggregation in Saccharomyces cerevisiae

Abstract: Selenomethionine, a dietary supplement with beneficial health effects, becomes toxic if taken in excess. To gain insight into the mechanisms of action of selenomethionine, we screened a collection of ≈5900 Saccharomyces cerevisiae mutants for sensitivity or resistance to growth-limiting amounts of the compound. Genes involved in protein degradation and synthesis were enriched in the obtained datasets, suggesting that selenomethionine causes a proteotoxic stress. We demonstrate that selenomethionine induces an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Regardless of its source, as coumaric acid is important in honey bee detoxification, future experiments determining its role in metal and metalloid tolerance and whether the microbiome has a role in production of the coumaric acid-like metabolite are needed. We also observed an increase in the abundance of short-chain peptides in selenate-exposed bees, which probably indicates that protein degradation occurred as a response to treatment (92), as selenium ions have been shown to increase protein degradation in cell models (93,94). Finally, we saw higher proportional abundances of the phospholipid precursor phosphocholine (95) and of two lysophosphatidylcholines-products of oxidized phospholipids (96)-in selenate treatments as well as MSEA results that indicated overexpression of phospholipid biosynthesis metabolites in both treatments.…”
Section: Toxicants Affect the Bee Microbiome And Metabolomementioning
confidence: 63%
“…Regardless of its source, as coumaric acid is important in honey bee detoxification, future experiments determining its role in metal and metalloid tolerance and whether the microbiome has a role in production of the coumaric acid-like metabolite are needed. We also observed an increase in the abundance of short-chain peptides in selenate-exposed bees, which probably indicates that protein degradation occurred as a response to treatment (92), as selenium ions have been shown to increase protein degradation in cell models (93,94). Finally, we saw higher proportional abundances of the phospholipid precursor phosphocholine (95) and of two lysophosphatidylcholines-products of oxidized phospholipids (96)-in selenate treatments as well as MSEA results that indicated overexpression of phospholipid biosynthesis metabolites in both treatments.…”
Section: Toxicants Affect the Bee Microbiome And Metabolomementioning
confidence: 63%
“…Bioavailability, toxicity and antioxidant activity of selenium depends on its chemical form. Selenomethionine is the most widely used form of Se in food and supplements, though it has less toxicity and excellent bioavailability but some reports show that its excessive use can lead to toxic effects [46]. Therefore, instead of selenomethionine Nano-Se can be used as its effect on upregulating glutathione peroxidase and thioredoxin reductase is comparable with selenomethionine with much lower toxicity [38].…”
Section: Therapeutic Efficacy Of Se Based Nanoparticlesmentioning
confidence: 99%
“…As these studies indicated, SeMet toxicity appears to come from two different mechanisms: SeMet likely generates reactive species, resulting in DNA damage 28 , consistent with the observation that SeMet could effectively inhibit the insect cell growth 17 . Alternatively, SeMet toxicity results from its metabolites, and a random incorporation of which promotes protein aggregation -SeMet causes proteotoxic stress resulting in cell death 29 . How does baculovirus infection reduce SeMet toxicity?…”
Section: Possible Mechanism Of Semet Toxicitymentioning
confidence: 99%